2009
DOI: 10.1007/s15010-008-8252-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatitis B Vaccination in Children Born to HBsAg-Positive Mothers: a 20-year Retrospective Study

Abstract: Our data, while confirming the effectiveness of anti hepatitis B vaccination, highlight the need for postvaccination follow-up, particularly in high-risk categories, to prolong protection, through booster doses if necessary. We show, moreover, the importance of maintaining active surveillance in the territory to improve follow-up to chronic carriers and to sensitize families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…Indeed, a similar observation was made on 100 subjects born to HBsAg positive mothers during 1984-2004, in whom 2% had anti-HBc and there were no carriers, yet only 63.3% of uninfected had anti-HBs 10 mIU/mL, the percentage of protected individuals decreasing with time with significant reduction of anti-HBs GMT after 5 years to reach 10 mIU/mL in about 15 years' time. 45 The situation was even more striking among Micronesians vaccinated at birth in that only 7.3% of uninfected individuals had positive antibody. 46 Thus even among complete vaccinees, vaccine-induced immunity should not be taken for granted from the time of adolescence onwards.…”
Section: Waning Of Anti-hbs Titer With Advancing Agementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a similar observation was made on 100 subjects born to HBsAg positive mothers during 1984-2004, in whom 2% had anti-HBc and there were no carriers, yet only 63.3% of uninfected had anti-HBs 10 mIU/mL, the percentage of protected individuals decreasing with time with significant reduction of anti-HBs GMT after 5 years to reach 10 mIU/mL in about 15 years' time. 45 The situation was even more striking among Micronesians vaccinated at birth in that only 7.3% of uninfected individuals had positive antibody. 46 Thus even among complete vaccinees, vaccine-induced immunity should not be taken for granted from the time of adolescence onwards.…”
Section: Waning Of Anti-hbs Titer With Advancing Agementioning
confidence: 99%
“…47 Nevertheless, disappearance of an anamnestic effect has been shown in many studies. 10,40,41,45,48 One study found that following a booster dose in subjects who received 4 doses of vaccine during infancy, 28.7% had undetectable anti-HBs, while HBsAg-specific IFN-g-or IL-5-secreting peripheral blood mononuclear cells remaining negative in 27.2%, and it was estimated that 10.1% of the total population had lost their vaccine-conferred booster response. 49 .…”
Section: Anamnestic Response In Vaccineesmentioning
confidence: 99%
“…However, recent studies have found that chronic HBV infection may occur 15 years after immunization in some areas where endemic infection is prevalent [8]. Less analogous data are known in low endemic countries [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed an anamnestic response to the booster dose administered more than 20 years after the primary vaccination in 95.8% of subjects, suggesting a strong persisting immune memory 19 . Two other studies have reported that protection provided by HBV vaccine persists for at least two decades in the great majority of vaccinated individuals 20,21 .…”
Section: Discussionmentioning
confidence: 96%